2023
DOI: 10.1590/fst.14722
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of quinoa-wheat flour blend for the preparation of dry cake

Abstract: The current study aimed at the quinoa-wheat composite flour's characterization (including total phenolics, total flavonoids, and antioxidant activity) as well as its effect on dry cake sensory quality. Findings revealed a rise in ash content, fat, protein, and crude fiber of composite-flour (0.56-1.23%, 1.13-1.76%, 10.14-11.02%, and 0.23-1.04%, respectively) with an increase of quinoa flour (5-20%). The addition of quinoa flour to the composite flour enhanced cake texture (0.26-.70 kg), but it also decreased L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
1
0
1
Order By: Relevance
“…During storage for up to 120 days, moisture did not change, possibly due to the package efficiency as a water vapor barrier. Our moisture values shown in Table 2 were below those found by Akhlaq et al (2023) in mixed flour with 10 and 20% of replacement of wheat flour for quinoa flour (12.83-13.53%).…”
Section: Physical-chemical Evaluation Of Mixed Flour Of Wheat and Boc...contrasting
confidence: 79%
“…During storage for up to 120 days, moisture did not change, possibly due to the package efficiency as a water vapor barrier. Our moisture values shown in Table 2 were below those found by Akhlaq et al (2023) in mixed flour with 10 and 20% of replacement of wheat flour for quinoa flour (12.83-13.53%).…”
Section: Physical-chemical Evaluation Of Mixed Flour Of Wheat and Boc...contrasting
confidence: 79%
“…Additionally, quinoa presents a lower amylase activity, which can increase the production of gas and thus the volume of bread [ 32 ]. Other studies [ 32 , 33 ] found similar data on the technological parameters of the bread and cakes with the addition of different quinoa particle sizes, with the bread volume decreasing with the reduction in the particle size. In this research, a rise of all reofermentometric parameters for wheat–quinoa composite flour dough was registered; this is due to fermentable sugars from quinoa flour and the indirect bread-making method.…”
Section: Discussionsupporting
confidence: 52%